2019
DOI: 10.1161/strokeaha.118.024076
|View full text |Cite
|
Sign up to set email alerts
|

Stent Design, Restenosis and Recurrent Stroke After Carotid Artery Stenting in the International Carotid Stenting Study

Abstract: Background and Purpose— Open-cell carotid artery stents are associated with a higher peri-procedural stroke risk than closed-cell stents. However, the effect of stent design on long-term durability of carotid artery stenting (CAS) is unknown. We compared the medium- to long-term risk of restenosis and ipsilateral stroke between patients treated with open-cell stents versus closed-cell stents in the ICSS (International Carotid Stenting Study). Methods— P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…On the contrary, closed-cell stents have tighter meshes, which may provide better coverage of the atheromatous lesion but are consequently more rigid. A recent study found that, compared with open-cell stents, the more rigid and more densely packed material in closed-cell stents might lead to greater irritation of the vessel wall, which in turn might stimulate neointima hyperplasia and result in a higher occurrence of restenosis (18). In this study, we found that the incidence of residual stenosis was higher for closed-cell stents than for open-cell stents, and different stent lengths did not influence residual stenosis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…On the contrary, closed-cell stents have tighter meshes, which may provide better coverage of the atheromatous lesion but are consequently more rigid. A recent study found that, compared with open-cell stents, the more rigid and more densely packed material in closed-cell stents might lead to greater irritation of the vessel wall, which in turn might stimulate neointima hyperplasia and result in a higher occurrence of restenosis (18). In this study, we found that the incidence of residual stenosis was higher for closed-cell stents than for open-cell stents, and different stent lengths did not influence residual stenosis.…”
Section: Discussionsupporting
confidence: 48%
“…CDU was performed within 1 week before and after CAS, and patients were followed-up for different periods (3,6,12,18,24, and 36 months) after CAS. The evaluation and detection of CDU was based on the vascular ultrasonography guidelines published by the Chinese Medical Doctor Association of Ultrasonography (9).…”
Section: Carotid Duplex Ultrasonographymentioning
confidence: 99%
“…In the literature, anatomical and technical risk factors for restenosis include the number of stents deployed, the presence of large and calcified plaques, and the existence of residual stenosis after the procedure or even the stent design used, to the detriment of stiffer stents with small cell sizes, but moderate radial force, such as WALLSTENT (Boston Scientific Corporation, Natick, MA, USA) [ 29 , 30 ]. Dyslipidemia, statin therapy, female sex, and smoking were associated with CAS restenosis as well [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Reported risk factors for ISR after CAS include aging,[ 1 , 6 , 8 , 12 ] smoking,[ 2 , 23 ] diabetes mellitus and dyslipidemia,[ 14 , 23 ] women,[ 12 , 14 , 23 ] hostile neck,[ 5 ] and prior neck cancer. [ 22 ] Stent-related factors, such as the diameter,[ 24 ] length,[ 16 ] type of stents (closed or open cell stent),[ 16 - 18 ] and multiple stent use,[ 12 ] are also possible risk factors for ISR after CAS.…”
Section: Discussionmentioning
confidence: 99%